Pembuatan Digital Storytelling dalam Pembelajaran Bahasa Jerman - Nurul Nabila; Indah Aini (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study employs the 4-D development model (Define, Design, Develop, and Disseminate) adapted from Thiagarajan et al. (1974) to develop a Digital Storytelling medium using Canva for the topic “Family” in Senior High School (SMA/MA). A needs analysis was conducted in the Define phase, revealing that students experienced difficulties in listening and speaking. In the Design phase, a context-based story medium with illustrations, texts, and German audio narration was created. During the Develop phase, the product was validated by two experts. A German language instructor reviewed the material and deemed it suitable for use without revisions. The material validation results showed that the medium is usable without revision, as the material was rated clear, systematic, complete, engaging, and easy to understand. The material expert’s evaluation covered five categories, resulting in a total material score of 95. A media expert evaluated the medium along with audio and video content. The media expert’s assessment included ten categories, resulting in a total media score of 95. Meanwhile, data validation indicated that the medium can be further used with minor revisions, such as enhancing visual elements to make it more dynamic and adjusting audio quality to improve listening comfort. The results of this study show that the development process of the Digital Storytelling medium using Canva for the “Family” topic in Senior High School successfully produced an engaging and communicative product that matches the characteristics of beginner German language learners. This medium contains a story on the theme “Family,” complemented by illustrations, texts, and audio content. The developed video has been uploaded to the YouTube platform to facilitate access for teachers and students.